Heart-Type Fatty Acid Binding Protein (H-FABP): Relationship with arterial ıntima-media thickness and role as diagnostic marker for atherosclerosis in patients with ımpaired glucose metabolism - Karbek, Basak (BioMed Central, 2011)
BACKGROUND: Heart type fatty acid binding protein (H-FABP) has been closely associated with acute coronary syndrome, cardiac abnormalities, stroke, and obstructive sleep disorder in previous studies. The aim of this study was to evaluate and compare the serum H-FABP levels and carotid artery intima-media thickness (CIMT) between patients with prediabetes and control subjects. RESEARCH DESIGN AND METHODS: We measured serum H-FABP levels in 58 prediabetic patients, 29 with impaired fasting glucose (IFG) and 29 with impaired glucose tolerance (IGT) and 28 age-, sex- and body mass index-matched control subjects using a sandwich enzyme-linked immunosorbent assay (ELISA), and in order to measure CIMT, all participants underwent high-resolution B-mode ultrasonography. RESULTS: Serum H-FABP levels were significantly elevated in pre-diabetic patients when compared with that of control subjects (IFG: 32.5 ± 34.2 ng/dL, IGT: 45.4 ± 45.8 ng/dL, control: 16.8 ± 14.9 ng/dL; p = 0.011). The difference in means of H-FABP levels between patients with IGT or IFG and control subjects was significant (p = 0.010 and p = 0.009, respectively). CIMT was higher in the pre-diabetic groups compared with the control group (IFG: 0.6 ± 0.1, IGT: 0.6 ± 0.1, control: 0.5 ± 0.1; p < 0.001), and H-FABP level was positively correlated with CIMT (p < 0.001, rho = 0.626). CONCLUSION: Our results indicate that patients with pre-diabetes are at increased risk for cardiovascular disease. In addition, serum H-FABP levels could represent a useful marker for myocardial performance in patients with IFG and IGT.